Pengendalian Superoxide Dismutase (SOD) dan Nitrit Oxide(NO) pada penderita DMT2 dengan emping garut (Maranta arundinacea Linn) sebagai makanan selingan - Betty Prastuti; Sunarti Sunarti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: Hyperglycemia in diabetes mellitus increases the production of superoxide that cause oxidative stress and decrease the activity of superoxide dismutase (SOD). SOD enzyme reduces superoxide to hydrogen peroxide to lessen the reaction between superoxide and nitric oxide (NO). To reduce hyperglycemia in diabetes mellitus, diabetics are encouraged to consume diet with low glycemic index. Arrowroot chips is a product commonly used by the community as a snack. Arrowroot has low glycemic index (glycemic index = 14) so it can be used as an alternative snack for diabetics.Objective: The aim of this study is to determine the beneficial effects of arrowroot chips to help controlling the blood glucose level, SOD activity and NO concentration in type 2 diabetes. Method: This is a quasi-experimental research with a one group pre test - post test. Subjects were 14 patients with type 2 diabetes mellitus who regularly visited endocrine polyclinic of RSUP.Dr. Sardjito Yogyakarta. The inclusion criteria were: aged 35-60 years, had suffered from diabetes mellitus for at least one year and currently on insulin injection therapy. The subjects were given 20 grams/day arrowroot chips to be consumed as a snack for four weeks. The blood samples were drawn before and after treatment. Glucose level were analyzed by GOD-PAP method, SOD activity was determined by Ransod kits and NO concentration was analyzed by colorimetric Gies reagent system. Finally, data were analyzed by paired t-test and correlation regression test.Result: There was an increased glucose level from 124,43 ± 33,56 to 139,00 ± 67,96 mg/dl after treatment (p=0,551), SOD activity decreased from 77,09 + 19,33 to 43,99 + 17,45 unit/ml whole blood after treatment (p=0,000), decreased NO concentration from 1,28 + 1,32 to 1,15 + 0,577 µM after treatment (p=0,875), and a positive correlation between SOD activity and NO concentration (p=0,151; r=0,405; R2=0,164).Conclusion: Arrowroot chips consumption as a snack for 4 weeks was unable to help controlling the fasting plasma glucose level, SOD activity and NO concentration in type 2 diabetics.